Construcción de un kart eléctrico y caracterización de su freno regenerativo (2017)
This project is a work done on the electric kart prototype of the BTA Racing Team of Universidad de Los Andes. The objectives of the project can be divided in two, first the construction of the electric kart making specially emphasis on its' electric systems, and secondly the characterization of its' regenerative brake. In terms of the construction the fist thing done was an overhaul of the kart in order the detect problems and thing to work on. Then a testing bench of the electric systems was installed, the purpose of this was to test the energy storage and power systems in order learn how they worked. During this process a parameter was found in the motor controller's programming that controlled the regenerative brake. Its' name is "Maximum torque applied when neutral braking" and it controls the intensity of the regenerative brake. When all the tests where done the two systems where installed again on the kart along side the rest of the mechanic and instrumentation components. In terms of the characterization a model was developed in which the dynamic and the regenerative brake concepts where mix together. The result was an estimate of the kart's autonomy for different values of the regenerative brake parameter. Finally on June 19 the kart was taken to the track in order to test the construction work and to obtain experimental data of the autonomy. During the test the kart was able to complete 20 laps where the parameter of regenerative brake was programed in 50% and 10%.--Tomado del Formato de Documento de Grado.